(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This study explores how idioms across diverse cultures reflect conceptualizations of life, revealing cultural values, beliefs, and worldviews. By analyzing idiomatic expressions in English, Chinese, Arabic, and Yoruba, we identify common themes and cultural-specific nuances in perceptions of life’s purpose, challenges, and temporality. Findings suggest that idioms serve as linguistic mirrors of cultural cognition, with universal themes like resilience and fate coexisting alongside culture-specific metaphors rooted in historical and environmental contexts. This cross-cultural analysis underscores the role of language in shaping and expressing human experience.